2020
DOI: 10.1513/annalsats.202002-136oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solriamfetol on Quality-of-Life Measures from a 12-Week Phase 3 Randomized Controlled Trial

Abstract: Rationale: Excessive daytime sleepiness in patients with obstructive sleep apnea is associated with substantial burden of illness. Objectives: To assess treatment effects of solriamfetol, a dopamine/norepinephrine reuptake inhibitor, on daily functioning, health-related quality of life, and work productivity in participants with obstructive sleep apnea and excessive daytime sleepiness as additional outcomes in a 12-week phase 3 trial ( www.clinicaltrials.gov … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…At baseline, about 49% of participants were employed, and presenteeism (working despite illness, etc., often resulting in reduced productivity) ranged from 43.5% to 47% across treatment groups. 46 , 47 Absenteeism was relatively low at baseline, with patients missing 2.6% to 5% of work per week. Activity impairment outside of work ranged from 37.8% to 44.3%.…”
Section: Clinical Efficacy Trialsmentioning
confidence: 98%
See 3 more Smart Citations
“…At baseline, about 49% of participants were employed, and presenteeism (working despite illness, etc., often resulting in reduced productivity) ranged from 43.5% to 47% across treatment groups. 46 , 47 Absenteeism was relatively low at baseline, with patients missing 2.6% to 5% of work per week. Activity impairment outside of work ranged from 37.8% to 44.3%.…”
Section: Clinical Efficacy Trialsmentioning
confidence: 98%
“…At baseline, about 49% of participants were employed, and presenteeism (working despite illness, etc., often resulting in reduced productivity) ranged from 43.5% to 47% across treatment groups. 46,47 37.8% to 44.3%. 46 At week 12, improved functioning and reduced impairment were observed with solriamfetol 150 mg and 300 mg doses on the basis of improvements in Functional Outcomes of Sleep Questionnaire (FOSQ) total score, overall work impairment, activity impairment, and physical component summary.…”
Section: Tones 3 (Osa)mentioning
confidence: 99%
See 2 more Smart Citations
“…Solriamfetol is a dopamine and norepinephrine reuptake inhibitor 1 approved in the United States and European Union to improve wakefulness in adult patients with excessive daytime sleepiness (EDS) associated with narcolepsy (75-150 mg/day) or obstructive sleep apnea (OSA; 37.5-150 mg/day). [2][3][4] In vitro studies have shown that the action of solriamfetol differs from that of traditional stimulants (eg, amphetamines) and other reuptake inhibitors (eg, modafinil). 1 Solriamfetol exhibits dual activity at dopamine and norepinephrine transporters and lacks monoamine-releasing effects associated with amphetamines.…”
mentioning
confidence: 99%